Pembentukan Model Keluarga Sadar Gizi (KADARZI) dan Kader Siaga Stunting sebagai Upaya Pemberdayaan Masyarakat Desa Sukogidri-Jember dalam Mengatasi Stunting - Sulistyaningsih, Erma; Dewanti, Parawita; Pralampita, Pulong Wijang (Universitas Nusantara PGRI Kediri, 2021)
Stunting is a major health problem in Indonesia. Sukogidri Village is one of the villages that contribute to stunting in Jember Regency. There are 18 stunting children under five from 353 total children under five in the village. The effort to solve the stunting problem should involve community participation through empowerment. This community service aimed to increase community empowerment to solve the stunting by forming the nutritionally-aware family (Keluarga Sadar Gizi = KADARZI) model and the stunting-alert cadres. KADARZI model was chosen in selected families and trained on the definition of KADARZI, the efforts and steps undertaken as a model for KADARZI in selected families. The stunting-alert cadres were formed from health cadres who were provided with intensive education and training materials on the stunting, its dangers and how to prevent it. After going through serial training, 10 KADARZI models and 10 stunting-alert cadres were formed in Sukogidri Village, Jember. It is hoped that the KADARZI model and stunting alert cadres will play an active role in overcoming stunting in the village.